2001
DOI: 10.1034/j.1600-0749.2001.140503.x
|View full text |Cite
|
Sign up to set email alerts
|

The Dilute Locus and Griscelli Syndrome: Gateways Towards a Better Understanding of Melanosome Transport

Abstract: would present a major breakthrough in the possibilities to In this review an overview of recent advances in the understanding of melanosome movement within epidermal influence pigmentation and related disorders, of great concern melanocytes is given. Exploration of the molecular events to some patients. Moreover, melanosome transport offers a good model to study mammalian organelle trafficking and its involved in and determining the process of melanosome transkey players in general. port, as an essential part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 69 publications
1
24
0
Order By: Relevance
“…The molecular motors involved in intracellular transport usually rely on the function of F-actin and/or myosin, and melanosomes are no exception [42,43]. In fact, the movement of melanosomes from the perinuclear region to the extremities of melanocytes (necessary for the subsequent transfer of melanosomes to neighboring keratinocytes) relies both on F-actin and on tubulin.…”
Section: Transport Of Melanosomes To the Dendrites And Transfer To Kementioning
confidence: 99%
“…The molecular motors involved in intracellular transport usually rely on the function of F-actin and/or myosin, and melanosomes are no exception [42,43]. In fact, the movement of melanosomes from the perinuclear region to the extremities of melanocytes (necessary for the subsequent transfer of melanosomes to neighboring keratinocytes) relies both on F-actin and on tubulin.…”
Section: Transport Of Melanosomes To the Dendrites And Transfer To Kementioning
confidence: 99%
“…In mice, there are three spontaneous mutations at the d locus that cause coat colour dilution and similar histomorphological changes as seen in CDA and BHFD. These are mutations in the leaden (ln, chromosome 1), the dilute (d, chromosome 9), and the ashen gene, 148 corresponding to the human Griscelli syndrome, a rare autosomal recessive disorder that is characterized by diffuse skin pigmentation, silvery hair, and the occurrence of either a primary neurological impairment or a severe immune disorder 149 . It has been shown that those three mutations are linked to defects in the intracellular transport mechanisms within cutaneous melanocytes.…”
Section: Congenital Alopecia In Domestic Animalsmentioning
confidence: 99%
“…This disease includes partial oculocutaneous albinism, with characteristic pigment clumping in hair shafts, and either neurological involvement or haemophagocytic syndrome, a process of uncontrolled T lymphocyte and macrophage activation leading to death in the absence of bone marrow transplantation. Recent evidence indicates that Griscelli syndrome results from mutations in the genes coding for either the unconventional myosin Va or the small GTPase rab27a [19][20][21]. Both of these proteins operate in the actin-rich periphery of melanocytes, where the head domain of myosin Va binds to actin filaments [7].…”
Section: Introductionmentioning
confidence: 99%